Reliability of carnitine concentrations measured in single postprandial urine samples from dogs - Sanderson, Sherry; Osborne, Carl; Lulich, Jody; Pierpont, Mary Ella; Gross, Kathy; Ogburn, Phillip; Koehler, Lori; Carvalho, Marileda [UNESP] (My University, 1996)
Objective - To evaluate the reliability of urine carnitine concentrations measured in single postprandial samples, compared with carnitine concentrations measured in 24-hour urine samples. Animals - 19 healthy Beagles. Procedure - After emptying the urinary bladder by catheterization, dogs were fed a canned canine maintenance diet. Approximately 8 hours later, urine, plasma, and serum samples were obtained for determination of urinary carnitine fractional excretion and urine carnitine-to-creatinine concentration ratio. Results were compared with 24-hour urinary carnitine excretion rate. Results - Fractional excretion of carnitine and urine carnitine-to-creatinine ratios correlated poorly with 24-hour urinary carnitine excretion. Conclusion - Determination of 24-hour urinary carnitine excretion is recommended to measure urine carnitine concentrations in dogs.
Keywords: biological marker; carnitine; animal; animal food; blood; comparative study; dog; female; male; orchiectomy; ovariectomy; postprandial state; reference value; reproducibility; urine; Animal Nutrition Physiology; Animals; Biological Markers; Carnitine; Dogs; Female; Male; Orchiectomy; Ovariectomy; Postprandial Period; Reference Values; Reproducibility of Results